Thermodynamic qualification of knitted spacer fabrics for use as insulation box insert in the context of refrigerated transport containers in the logistics sector - Julia Klausmann; Thomas Mutschler; Prisca Holderied; Dominik Güther; Thomas Freitag; Matthias Hummel; Martin Zeitler; Oliver van Neerven; Marcus Oliver Weber; Christof Breckenfelder (Communications in Development and Assembling of Textile Products)
Temperature-sensitive products such as refrigerated and frozen goods pose particular challenges for logistics. Against the background of the mobility shift towards electric vehicles and the current challenges of temperature-stable transport in the field of pharmaceutical, esp. vaccine logistics in the context of the SARS-CoV-2 pandemic, new, energy-efficient vehicle equipment is needed to maintain cold chains. Known refrigeration concepts are designed to cool the entire cargo hold. In addition, the goods cannot be removed from the vehicle while maintaining the cold chain. An insulating effect of containers is typically achieved by using foamed polystyrene (Styrofoam). On the one hand, these structures have a very good insulating effect, but on the other hand, they cannot be reduced in volume during recirculation and are problematic with regard to recycling. The aim of the research presented here is therefore to develop a knitted box that is designed as a volume-reducible, rigid but foldable box. This can be used as a supplement to existing transport container systems and therefore can be inserted in the transport container. The knitted box performs as insulation when the transported goods are actively cooled inside the box, which is more sustainable and flexible than recent insulation solutions. Knitted fabrics, especially spacer fabrics, have advantageous thermo-physical properties for this application due to their structural design. In the course of a research project, various spacer fabrics were tested for their thermo-physical suitability as insulation materials. It was found that knitted predetermined folding lines represent an insulation gap. Based on this, a new structure was developed which, due to its structural design, compensates for cold or thermal bridges at vertices and edges of the box. The results show that the knitted corrugated structure insulates better than the knitted spacer fabrics with predetermined folding lines. A thermal imaging camera was used to identify critical points for heat transfer.